Strategies to Modify the Risk of Heart Failure Readmission: A Systematic Review and Meta-Analysis. (30th March 2017) - Wan, Thomas T. H.; Terry, Amanda; Cobb, Enesha; McKee, Bobbie; Tregerman, Rebecca; Barbaro, Sara D. S.
Background: Human factors play an important role in health-care outcomes of heart failure (HF) patients. A systematic review and meta-analysis of clinical trial studies on HF hospitalization may yield positive proofs of the beneficial effect of specific care management strategies. Purpose: To investigate how the 8 guiding principles of choice, rest, environment, activity, trust, interpersonal relationships, outlook, and nutrition reduce HF readmissions. Basic Procedures: Appropriate keywords were identified related to the (1) independent variable of hospitalization and treatment, (2) the moderating variable of care management principles, (3) the dependent variable of readmission, and (4) the disease of HF to conduct searches in 9 databases. Databases searched included CINAHL, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, ERIC, MEDLINE, PubMed, PsycInfo, Science Direct, and Web of Science. Only prospective studies associated with HF hospitalization and readmissions, published in English, Chinese, Spanish, and German journals between January 1, 1990, and August 31, 2015, were included in the systematic review. In the meta-analysis, data were collected from studies that measured HF readmission for individual patients. Main Findings: The results indicate that an intervention involving any human factor principles may nearly double an individual's probability of not being readmitted. Participants in interventions that incorporated single or combined principles were 1.4 to 6.8 times less likely to be readmitted. Principal Conclusions: Interventions with human factor principles reduce readmissions among HF patients. Overall, this review may help reconfigure the design, implementation, and evaluation of clinical practice for reducing HF readmissions in the future.